Pooling sovereignty risks: The case of environmental treaties and international debt - Ernst Mohr; Jonathan P. Thomas (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
A model is analysed in which a sovereign country has independent obligations to repay a creditor bank and to keep an environmental treaty. It is shown that the linkage of both obligations through a cross-default contract may reduce the sovereign risk attached to both the debt and the environmental contracts. Moreover, such a linkage will create an incentive for the sovereign and the bank to engage in a debt-for-natureswap, the anticipation of which increases the initial incentive for a cross-default contract to be entered into.
Keywords: 330